In adolescents with epilepsy, high scores of anxiety and depression are associated with occurrence of seizures in public places - Nathália F. Siqueira; Fernando L. B. B. Oliveira; Jorge A. Siqueira; Elisabete Abib Pedroso de Souza (Arquivos de Neuro-Psiquiatria)
Objective To assess depression and anxiety symptoms of adolescents with epilepsy compared with adolescents without epilepsy. Method The study sample consisted of: case participants (50 subjects) attending the pediatric epilepsy clinic of a tertiary hospital and control participants (51 subjects) from public schools. The instruments utilized were: identification card with demographic and epilepsy data, Beck Depression Inventory and State-Trait Anxiety Inventory. Results No significant differences were founded between the groups regarding scores for depression and anxiety symptoms but both groups presented moderate scores of anxiety. A correlation was found between low scores anxiety and not frequent seizures, low scores anxiety and perception of seizure control, high scores of anxiety and depression and occurrence of seizures in public places. Conclusion Low scores of anxiety are associated with not frequent seizures; high scores of anxiety and depression are associated with occurrence of seizures in public places.